Kepuasan Wisatawan Dipengaruhi Oleh Kualitas Pelayanan dan Fasilitas di Hotel The Swarga Suites Bali - Pande, Agus Padya Mahardika; Wirya , I Made Suwitra; Susila, I Made Gede Darma (Universitas Triatma Mulya, 2025)
The evaluation of Customer Satisfaction serves as a pivotal metric delineating the comprehensive response to product or service attributes. Favorable perceptual responses engender sustained consumer loyalty. This scholarly investigation scrutinizes the multifaceted influence of Quality Of Services and Facilities Towards Customer Satisfaction, elucidating predominant variables and assessing correlational dynamics within the hospitality context. Conducted at The Swarga Suites Bali Berawa, the empirical research employed observational and questionnaire-based methodologies, encompassing 80 respondents from the Canggu hospitality landscape. Utilizing Descriptive Statistical Analysis and Multivariate Linear Regression, the investigation reveals that Quality Of Services and Facilities Towards demonstrate a statistically significant, positively correlated impact on Customer Satisfaction. Notably, the Facilities Towards variable emerges as the predominant determinant of consumer satisfaction. Recommendations for The Swarga Suites Bali Berawa management include: implementing rigorous personnel supervision, strategically enhancing indoor infrastructure, and refining service protocols to optimize guest experiential satisfaction.